(untitled) (Global Journal of Human-Social Science, 2012)
The study seeks to obtain the impact of internship programme on the performance of public health care institutions Contextual factors are sought that influence the relationship impact and effect between internship programme and performance of public healthcare institutions The research design adopted is descriptive survey through both qualitative and quantitative data This study is conducted in Kakamega County western region of Kenya The population of the study is 2225 with a stratified randomly selected sample of 444 respondents Primary data is collected through questionnaires while secondary data is sourced from official hospital records journals text books and internet articles Data is analyzed using descriptive and inferential statistics The study concludes that internship programme influences performance of public healthcare institutions